Combination of Blue Diode Laser and Ag NPs Nanophotosensitizer with Grape Seed Bioreductor to Overcome Biofilm Resistance - Yaqubi, Ahmad Khalil; Astuti, Suryani Dyah; Rakhman, Nida Ardianti; Aquilera, Crysant; Zaidan, Andi Hamim; Abd Razak, Nasrul Anuar (Trends in Sciences, 2025)
Introduction: Indonesia faces significant health issues due to infection caused by microorganisms. Microbial resistance is increasing, leading to the use of Photodynamic Inactivation, a therapeutic method generating reactive oxygen species. The study evaluates the effectiveness of blue laser and silver nanoparticles synthesized from grape seed as photosensitizers in reducing bacterial biofilms, common pathogens for infections; Materials and methods: The study involved 4 groups of samples: T0, A1 and A2, A3 and A4, and A2 and A4, each exposed to silver nanoparticles and treated with grape seed as a photosensitizer to investigate the effects of laser irradiation on biofilms. The samples were irradiated for 90, 120, 150 or 180 s. Following irradiation, the samples were cultured on TSA media and incubated for 24 h at 37 °C. The number of bacterial colonies was determined using total plate count (TPC). The data obtained were analyzed using a 2-way ANOVA factorial statistical test, followed by Tukey’s Post Hoc Test, with p < 0.05; Results and discussion: Adding 2 mM, AgNPs-GSE produced the highest percentage of bacterial biofilm inactivation. Specifically, Escherichia coli biofilms showed a 72.59 % reduction, while Staphylococcus aureus biofilms exhibited an 86.74 % reduction after 180 s of irradiation at a dose of 3.43 J/cm2; and Conclusions: The study demonstrates that irradiation with a blue diode laser at a dose of 3.43 J/cm2 for 180 s, combined with the AgNPs-GS photosensitizer, provides bacterial biofilms’ most optimal and efficient inactivation. HIGHLIGHTS The blue laser, combined with AgNPs-GSE, achieved up to 86.74 % reduction in bacterial biofilms. The grape seed extract facilitated the eco-friendly synthesis of silver nanoparticles, highlighting its green chemistry approach. An energy density of 3.43 J/cm2·s proved highly effective in reducing biofilms, offering a promising solution for combating resistant E. coli and S. aureus. This innovative method integrates nanotechnology and laser therapy, paving the way for advanced antimicrobial treatments. GRAPHICAL ABSTRACT